Corneal epithelial debridement for the treatment of painful bullous keratopathy: A pilot study - McClunan, Daemon (Division of Ophthalmology, 2019)
Purpose: The aim of the study was to evaluate the outcomes of corneal manual epithelial debridement (MED) for the treatment of painful bullous keratopathy (BK). Methods: In a prospective interventional case series, 15 eyes of 15 consecutive patients presenting with painful BK of varying aetiology underwent MED. Patients were followed up at 10 days, 1 month, 2 months, 3 months and 6 months post procedure. Outcome parameters evaluated include numeric rating pain score (NRS), visual acuity (VA), corneal transparency and size of corneal bullae. Results: The mean NRS was significantly decreased from its baseline value of 7.2 +- 1.7 at all follow-up visits (p < 0.02). Mean VA and corneal transparency remained stable for the duration of the study. In most patients the average size of corneal bullae was initially reduced, but returned to baseline by the end of the study. Conclusion: MED reduces mean pain scores and temporarily reduces the size of corneal bullae in BK. MED may be considered as a simple, low cost alternative for reducing pain in patients awaiting corneal transplant. Further studies are required to evaluate MED for the treatment of BK and compare outcomes against other palliative treatment options.